Le conservateur de musée de province de la IIIe République : vers une professionnalisation ? - Géraldine Masson (In Situ)
The Third Republic enabled French museums to become a place of cultural education similar to that of schools. A national, federated network of museums was established for national collections of art in the early 20th Century, during the rise of provincial museums. The French state sought to display a self-legitimizing, civic-mindedness and to teach lessons of history of the Nation and national heritage to its citizens. More than an institutional history of the rise of provincial museums, this study demonstrates the involvement of the curators of provincial museums in the development of that policy and shows how it led to the creation of an organized profession. Utilizing the report of the parliamentary commission for French museums created in 1905, 263 curators in charge of state sponsored long-term loans were identified and studied. They had to cope with locally specific issues, particularly financial restrictions and local politics, but succeeded in fashioning a new way of working that was agreed to by all colleagues in provincial institutions as well as French national museums, such as the musée du Louvre, when museology was created.